Political Communication and Leadership Image of Ning Ita for Success in Two Periods the Mojokerto City - Ayu Fatmala Agustin; Syavira Dwi Kumala Putri; Nik Nur Nazira Arisya Bt Nik Nazman (Journal of Religion, Local Politics, and Law, 2025)
Ning Ita's success in leading the city of Mojokerto for two periods is an interesting phenomenon in political sociology, especially in the context of political communication and leadership image formation. Leaders who can build effective communication tend to gain strong legitimacy from the community, thereby maintaining the sustainability of their leadership. This study aims to analyze Ning Ita's political communication strategy and its contribution to a positive image among the public. Using the theory of political communication as a foundation, the research was conducted with a qualitative approach through documentation studies and in-depth interviews for comprehensive data. The results showed that Ning Ita implemented a systematic communication strategy through mass media, social media, and direct interaction with the community. Consistency in delivering clear, transparent, and participatory political messages is the main factor shaping his image as a responsive, innovative, and close to the People leader. Effective political communication has an impact on increasing public confidence and political stability, favoring the sustainability of its leadership. In conclusion, political communication is not just a tool to deliver policies, but a strategic element to build an image of sustainable leadership and strengthen the relationship between leaders and society